Common Knowledge - Greco, John (International journal for the study of skepticism, 2016)
A promising idea in the recent literature is that the concept of knowledge serves to govern the flow of actionable information within a community of information sharers. In this connection, several authors have argued that knowledge is the “norm of assertion,” while others have explored the distinctive role of testimony in the transmission of knowledge. This paper investigates the role of “common knowledge” in such a community, and compares it to Wittgenstein’s notion of “hinge propositions” in On Certainty. Wittgenstein’s thinking is evaluated in this context, and an account of common knowledge along Wittgensteinian lines is considered. I do not here endorse the account of common knowledge that results. Rather, I consider some of the advantages and disadvantages of what looks to be a promising approach.